The prawn Macrobrachium vollenhovenii in the Senegal River basin: towards sustainable restocking of all-male populations for biological control of schistosomiasis. - Amit Savaya Alkalay; Ohad Rosen; Susanne H Sokolow; Yacinthe P W Faye; Djibril S Faye; Eliahu D Aflalo; Nicolas Jouanard; Dina Zilberg; Elizabeth Huttinger; Amir Sagi (Public Library of Science (PLoS), 2014)
Early malacological literature suggests that the outbreak of schistosomiasis, a parasitic disease transmitted by aquatic snails, in the Senegal River basin occurred due to ecological changes resulting from the construction of the Diama dam. The common treatment, the drug praziquantel, does not protect from the high risk of re-infection due to human contact with infested water on a daily basis. The construction of the dam interfered with the life cycle of the prawn Macrobrachium vollenhovenii by blocking its access to breeding grounds in the estuary. These prawns were demonstrated to be potential biological control agents, being effective predators of Schistosoma-susceptible snails. Here, we propose a responsible restocking strategy using all-male prawn populations which could provide sustainable disease control. Male prawns reach a larger size and have a lower tendency to migrate than females. We, therefore, expect that periodic restocking of all-male juveniles will decrease the prevalence of schistosomiasis and increase villagers' welfare. In this interdisciplinary study, we examined current prawn abundance along the river basin, complemented with a retrospective questionnaire completed by local fishermen. We revealed the current absence of prawns upriver and thus demonstrated the need for restocking. Since male prawns are suggested to be preferable for bio-control, we laid the molecular foundation for production of all-male M. vollenhovenii through a complete sequencing of the insulin-like androgenic gland-encoding gene (IAG), which is responsible for sexual differentiation in crustaceans. We also conducted bioinformatics and immunohistochemistry analyses to demonstrate the similarity of this sequence to the IAG of another Macrobrachium species in which neo-females are produced and their progeny are 100% males. At least 100 million people at risk of schistosomiasis are residents of areas that experienced water management manipulations. Our suggested non-breeding sustainable model of control-if proven successful-could prevent re-infections and thus prove useful throughout the world.